Empathy or entitlement? Humanizing and Othering discourses in Go Back To Where You Came From. Issue 1 (1st April 2014) - Price, Emma
Debate over asylum seekers and refugees has continued over several decades in Australia. Terms such as 'boat people', 'illegal immigrants' and 'queue jumpers' have peppered more recent discussions, as well as political party rhetoric such as 'stopping the boats' and a network of 'people smuggling'. In 2011 SBS (Australia) broadcast the first series of a reality TV-type programme entitled Go Back To Where You Came From in which a group of 'ordinary Australians' followed a refugee journey in reverse. This 'alternative' format for exploring a controversial Australian issue suggests the potential for a more humanitarian perspective and a different kind of engagement with audiences as opposed to news or documentary. This article however examines discourses of the 'Other' still present within the programme, including the representation of 'ordinary Australians' as potential opportunities for empathy, but also as possible perpetuation of the dominant negative portrayals of refugees and asylum seekers in Australia. Utilizing Said and Bhabha's theories of Orientalism and the Other, this article combines research on media representation of refugees with Hage's argument about the construction of 'paranoid nationalism' through care and worry, to examine the tensions in Go Back To Where You Came From between humanitarian inclusion and exclusion, and between legitimacy and deviance.